How can a central bank exit quantitative easing without rapidly shrinking its balance sheet? - Atsushi Tanaka (Central Bank Review (CBR), 2022)
An important question for the major central banks of the industrialized world is how to design desirable strategies to exit quantitative easing (QE). At the exit, if a central bank needs to reduce rapidly the liquidity created by its balance sheet expansion, issuing new interest-bearing liabilities would be preferable to rapidly shrinking the balance sheet by selling existing assets, both for the stability of those assets' markets and to be able to keep capital losses from being reflected in the balance sheet under amortized-cost accounting. Given that existing assets accumulated during the quantitative easing period have low interest returns, and new liabilities to be issued in the quantitative tightening period would have high interest payouts, the central bank may run a loss that may threaten its solvency, which may force the bank to expand the monetary base above the level that is consistent with the central bank's ideal price stability path. This study considers a central bank that exits QE by issuing liabilities and examines an optimal exit strategy while maintaining the solvency by constructing a simple dynamic optimization model. The model is then applied to the Bank of Japan and the Federal Reserve to examine their possible exits.
Keywords: E52; E58; 330; Central bank; Monetary base; Inflation; Quantitative easing; Exit strateg; Solvency